2011
DOI: 10.1016/j.jpcs.2011.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Superparamagnetic-like behavior and spin–orbit coupling in (Co,Zn)RE4W3O16 tungstates (RE=Nd, Sm, Eu, Gd, Dy and Ho)

Abstract: Magnetic susceptibility measurements carried out on (Co,Zn)RE 4 W 3 O 16 compounds revealed a disordered state of magnetic moments above 4.2 K for all compounds under study, and a weak response to magnetic field and temperature for ZnSm 4 W 3 O 16 and ZnEu 4 W 3 O 16 samples. The temperature independent component of magnetic susceptibility has a negative value for ZnGd 4 W 3 O 16 and a positive one for the rest of the tungstates, indicating a domination of van Vleck contribution. The magnetization isotherms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…Our studies on electrical and magnetic properties of new tungstates [21][22][23][24][25][26][27][28], molybdates [29][30][31], and molybdato-tungstates [28,32,33] doped with rare earth ions (RE 3+ ) and obtained both in the form of nano-, micropowders, and single crystals have shown that they are non-conductive paramagnetics or superparamagnetics. The reason for this is the strong electron screening on 4f-shells.…”
Section: Introduction mentioning
confidence: 99%
See 1 more Smart Citation
“…Our studies on electrical and magnetic properties of new tungstates [21][22][23][24][25][26][27][28], molybdates [29][30][31], and molybdato-tungstates [28,32,33] doped with rare earth ions (RE 3+ ) and obtained both in the form of nano-, micropowders, and single crystals have shown that they are non-conductive paramagnetics or superparamagnetics. The reason for this is the strong electron screening on 4f-shells.…”
Section: Introduction mentioning
confidence: 99%
“…The reason for this is the strong electron screening on 4f-shells. In turn, dielectric spectroscopy studies have shown that these new materials containing additionally d-electron metal ions with unfilled 3d-shells have a bigger capacity for charge accumulation, which is usually accompanied by bigger energy loss [22,23]. Among the paramagnetic rare earth ions, gadolinium ion (Gd 3+ , 4f 5 ) possesses a large magnetic moment due to its isotropic electronic ground state of 7/2 S. Because of the excellent magnetic resonance imaging effect observed for Gd 3+ ions they are used as a common MRI contrast agent [34][35][36].…”
Section: Introduction mentioning
confidence: 99%
“…[6] and J is dened as a sum of an eective angular momentum of RE 3+ ions and the eective spin of Cu 2+ ones. The latter results from the fact that the JLS -coupling works for the protected RE 4f -shell, but not for the unprotected TM 3d-shell [9]. The values of p eff presented in Table show [11], and MPr 2 W 2 O 10 (M = Cd, Co, Mn) [12] ones.…”
Section: Resultsmentioning
confidence: 96%
“…In all cases above mentioned, the RE 3+ ions are mainly responsible for the paramagnetic state while the inuence of the transition metal (TM) ions on the magnetic properties is slight. The latter strongly inuence on the electronic properties because the TM 3+ ions, as Cu 2+ , Co 2+ , Mn 2+ have both unlled and unscreened 3d-shells [5,9,12].…”
Section: Resultsmentioning
confidence: 99%
“…Also a strong spin orbit coupling visible in the large value of the Landé factor g χ = 2.72 may exist, too. A superparamagnetism was not stated in the CuCr 1.65 Se 4 nanoparticles since the magnetization curves were deviated from the universal function of magnetization vs. magnetic eld divided by the temperature [13]. …”
Section: Resultsmentioning
confidence: 99%